2020
DOI: 10.1186/s12884-020-03284-1
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy complications among nulliparous and multiparous women with advanced maternal age: a community-based prospective cohort study in China

Abstract: Background This study aimed to evaluate the incidence rates and risks of pregnancy complications among nulliparous and multiparous women with advanced maternal age (AMA, ≥35 years) in China. Methods We performed a community-based prospective cohort study of 10,171 pregnant women in selected two sub-districts and 11 towns of Liuyang from 2013 to 2015. All subjects were followed up from the first prenatal care (at ≤12 weeks) to delivery, and risks of pregnancy complications were compared by parity and maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
7
19
0
2
Order By: Relevance
“…Multi and grand-multiparous pregnant women were more liable to develop VI than those who were nulli and primiparous. This finding is supported by a previous study in the USA [ 15 ], Croatia [ 23 ], and China [ 20 ]. This event is probably accounted for the repeated ocular alteration in the succeeding gravidity of mothers who had a greater number of parity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Multi and grand-multiparous pregnant women were more liable to develop VI than those who were nulli and primiparous. This finding is supported by a previous study in the USA [ 15 ], Croatia [ 23 ], and China [ 20 ]. This event is probably accounted for the repeated ocular alteration in the succeeding gravidity of mothers who had a greater number of parity.…”
Section: Discussionsupporting
confidence: 89%
“…According to the previous studies in the globe, VI has a cross relation with the age of pregnant women [ 1 , 14 , 15 ], residence [ 1 , 16 ], educational status [ 17 – 19 ], occupation [ 20 , 21 ], gestational age (GA) [ 7 , 15 , 22 ], maternal parity [ 15 , 20 , 23 ], diabetes mellitus [ 24 , 25 ], gestational diabetes mellitus (GDM) [ 14 , 20 ], pre-existing hypertension [ 12 , 20 ], pregnancy-induced hypertension (PIH) [ 14 , 20 ], family history of vision problem [ 26 ], prolonged use of smart phones and computers [ 27 29 ], medication history [ 14 , 30 , 31 ], and history of contraceptive use [ 14 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al identified the incidence rates of pregnancy complications in nulliparous and multiparous Chinese women of advanced maternal age using a community-based prospective cohort. The findings suggested that women of advanced maternal age should be regarded as at high risk for pregnancy complications, including HDP [ 19 ]. A large cohort of Japanese women with singleton pregnancies also indicated that advanced maternal age was a risk factor for HDP [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the incidences of spontaneous abortion, ectopic pregnancy, stillbirth, and fetal chromosomal abnormalities in older pregnant women (≥35 years old) are also increased. The incidences of gestational diabetes mellitus, hypertensive disorder complicating pregnancy, abnormal amniotic fluid volume, placenta previa, postpartum hemorrhage, and multiple pregnancy are also significantly increased ( Lean et al, 2017 ; Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%